A Comparison of Different Tissues Identifies the Main Precursors of Volatile Substances in Chicken Meat - Luo, Na; Liu, Li; Yuan, Xiaoya; Jin, Yuxi; Zhao, Guiping; Wen, Jie; Cui, Huanxian (Frontiers in Physiology, 2022)
Amino acids and fatty acids are the main precursors of volatile organic compounds (VOCs) in meat. The purpose of this study was to determine the main VOC components in chicken breast muscle (BM) and abdominal fat (AF) tissue, as well as the source of VOCs, to provide a basis for quality improvement of broilers. BM and AF served as experimental and control groups, and gas chromatography-mass spectrometry (GC-MS) and untargeted metabolomics were employed to identify the source of VOCs. The results revealed nine VOCs in BM and AF tissues, including hexanal, octanal, and nonanal. VOCs including 1-octen-3-ol, (E,E)-2, 4-nonadienal, and benzaldehyde were significantly elevated in BM compared with AF (p < 0.05), while heptane and diethyl disulphide showed the opposite trend (p < 0.05). Levels of hexanal, heptanal, and octanal were similar in the two tissues. Metabolites of VOCs in chicken BM were investigated by weighted co-expression network analysis. However, only blue module in BM tissue was positively correlated with hexanal (r = 0.66, p = 0.01), heptanal (r = 0.67, p = 0.008), and (E,E)-2,4-nonadienal (r = 0.88, p = 3E-05). L-tyrosine, L-asparagine, adenosine, and valine were the main precursors of (E,E)-2,4-nonadienal and heptanal in BM tissue. Amino acids are the main precursors of 1-octen-3-ol, (E,E)-2, 4-nonadienal, and heptanal in chicken meat, while fatty acids are the main precursors of diethyl disulfide. However, hexanal can be synthesized from amino acids and small amounts of fatty acids as precursors. These findings expand our understanding of VOCs in chicken.